2014
DOI: 10.1016/j.pneurobio.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish models of human motor neuron diseases: Advantages and limitations

Abstract: Motor neuron diseases (MNDs) are an etiologically heterogeneous group of disorders of neurodegenerative origin, which result in degeneration of lower (LMNs) and/or upper motor neurons (UMNs). Neurodegenerative MNDs include pure hereditary spastic paraplegia (HSP), which involves specific degeneration of UMNs, leading to progressive spasticity of the lower limbs. In contrast, spinal muscular atrophy (SMA) involves the specific degeneration of LMNs, with symmetrical muscle weakness and atrophy. Amyotrophic later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 291 publications
5
125
0
Order By: Relevance
“…These animal models have been evaluated in detail in several recent reviews [131][132][133][134][135]. The mutant SOD1 transgenic mouse model developed in the mid-1990s was a major advance because these transgenic animals exhibit adult-onset clinical signs resembling those seen in ALS patients, including muscle wasting initiated by motor neuron death and paralysis of limbs [136,137].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These animal models have been evaluated in detail in several recent reviews [131][132][133][134][135]. The mutant SOD1 transgenic mouse model developed in the mid-1990s was a major advance because these transgenic animals exhibit adult-onset clinical signs resembling those seen in ALS patients, including muscle wasting initiated by motor neuron death and paralysis of limbs [136,137].…”
Section: Reviewmentioning
confidence: 99%
“…Animal models, from yeast to the invertebrates Drosophila and C. elegans, have been used to model the majority of the genetic causes of ALS and FTD [132][133][134]. Similarly, the majority of the ALS and FTD genes have recently been functionally characterized using the vertebrate model zebrafish [131][132][133][134][135][136][137][138][139][140][141][142][143]. These animal models are more efficient than mammalian models at defining the pathogenicity of rare variants found in ALS/ FTD patients, evaluating the degree of interactions among causative genes, and identifying risk factors.…”
Section: Reviewmentioning
confidence: 99%
“…In the field of developmental biology, many studies have demonstrated that zebrafish and human show marked similarity in hematopoiesis 3 , hemostasis 4,5 , and myelopoiesis 6 . Adult zebrafish are also used for studying immunological 7 , neurodegenerative 8 and obesityrelated diseases 9 because this model organism shares common pathways with those disrupted in human diseases. For obesity and obesityrelated diseases (diabetes, hepatic steatosis and nonalcoholic steatohepatitis and atherosclerosis), zebrafish blood glucose and lipids levels have been thoroughly investigated in several transgenic and diet-induced obesity models [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth of remembering that other non-mammalian animal models have also been integrated to the study of MN degenerative diseases: invertebrates such as the worm (Coenorabditis elegans) (Sleigh et al, 2011;Therrien and Parker, 2014) and the fruit fly (Drosophila melanogaster) (Wang et al, 2011;Cherry et al, 2013) and vertebrates (the zebrafish, Danio rerio) (Babin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%